Literasi Aksara Jawa untuk Penguatan Citra Diri dan Produk Budaya Sanggar Seni Larasati Purbalingga - Exwan Andriyan Verrysaputro; Kilau Riksaning Ayu; Ashlikhatul Fuaddah; Haryono Haryono (BULETIN ILMIAH NAGARI MEMBANGUN, 2025)
Larasati Art Studio in Purbalingga represents a cultural community with significant potential in performing arts and local heritage preservation. However, the studio faces challenges in leveraging literacy-related competencies, particularly in Javanese script, for cultural product development and digital marketing. This gap limits the studio’s ability to strengthen its image as a center for Javanese cultural preservation at the Banyumas Regency level. This study aims to enhance the studio’s capacity in Javanese script literacy and cultural product creation. A community service program was conducted involving 45 participants, utilizing lectures, group discussions, demonstrations, and hands-on practice to produce handicrafts incorporating Javanese script. Pre- and post-training evaluations were administered to assess literacy improvement and skill acquisition. The results indicate a significant increase in participants’ literacy and product-making abilities, with the average pre-training score of 61.47% improving to a post-training score of 84.33%. Participants successfully produced 50 cultural handicraft items integrating Javanese script, which were subsequently documented and promoted through digital platforms. These outcomes demonstrate that structured literacy training and practical product development can effectively strengthen the studio’s public image and enhance its role in cultural preservation. In conclusion, the program successfully improved Javanese script literacy, facilitated cultural product creation, and reinforced Larasati Art Studio’s function as an inheritor, preserver, and developer of local Javanese culture. The study recommends continued literacy-based interventions to sustain cultural engagement and community empowerment.